Carnivore coprolites from “Gruta del Indio” site as source of paleoparasitological and paleoecological evidences (late Pleistocene-Holocene, Mendoza, Argentina) - Bellusci, Agustín (2021)
In the southern cone of South America, inhabit a large diversity of Neotropical carnivores. Carnivore coprolites are a valuable source of paleoecological and paleoparasitological information. The rock shelter Gruta del Indio (GI) is an emblematic archeological and paleontological site located from Mendoza, Argentina. Several studies were conducted at this site, which provided a stratified sequence spanning the last ∼31 ky BP. The aim of this work was to study parasite remains found in coprolites assigned to carnivores from GI, with the purpose of contributing to the paleoecological knowledge of the site. Twenty coprolites were examined for parasites. Samples were rehydrated in a 0.5% water solution of trisodium phosphate, then homogenized, filtered, and processed by spontaneous sedimentation. The macroscopic remains were separated and dried at room temperature and were examined for diet analysis. All micromammal prey belonged to the Order Rodentia, and six histricomorphs could be identified. Also, bird bones, plant, arthropod, and hair remains were found. Five coprolites contained parasite remains, and eight nematode species were recovered. This is the first paleoparasitological study at this site, and the findings broaden the knowledge of the biogeographic history of the gastrointestinal helminths found. The obtained results evidence the importance of carnivore coprolite studies recovered from archeological contexts in the reconstruction of paleoecological scenarios. Also, the importance of carnivores for the dispersion of their own parasites and the parasites of their prey are discussed. These parasitological findings contribute with the study of the presence of potential parasitic zoonoses in the Holocene.